Catastrophes on Stage: Interurban Connections in Disaster Prints of the Late Eighteenth Century. (2nd April 2020) - van Asperen, Hanneke
Abstract : Prints depicting disasters were produced to create visible and explicit markers of memorable events. In this essay, a print with an allegory of a fire in Amsterdam's Schouwburg theatre is used to investigate this particular function of disaster prints, first by looking closely at the iconography and then at the larger network of disasters that were used as points of reference after the fire. The print serves as a starting point for investigating the deeper impact of images in the longer term. The same format was adopted 35 years later, in a print depicting the explosion of a gunpowder ship in the heart of the city of Leiden. It seems that the allegory of the fire gave the artist the same possibilities of visualising communally felt feelings of loss. Furthermore, the print of the Leiden explosion was consciously designed to evoke memories of a fire in Amsterdam where its primary audience was located. These destructive disasters had an impact that transcended towns and regions, and prints referred back to disasters in the past to communicate impact of recent events. In the Leiden print, meant for an Amsterdam audience, the usual points of reference were complemented with an image of a local disaster, i.e. the Schouwburg fire, to underline and encourage interurban connections. This allusion to a carefully chosen disaster in the past helped evoke an appropriate response to a catastrophe in the present. This art historical study offers insight into the importance of images in disaster responses and demonstrates how disaster prints could stimulate interurban charity by evoking familiar pictures of local catastrophes.